Traditions and modern directions of scientific research at the faculty of economics of the Belarusian State University - Lavruhina, Irina A. (Journal of the Belarusian State University. Economics, 2019)
The main directions of modern scientific research at the faculty of economics of Belarusian State University are put forward. The connection with the previous stages of development of economics in Belarusian State University for its more than 75-year history, as well as the contribution to economics of scientists of Belarusian State University are reflected.
Keywords: national (domestic) economic science; economic research direction; scientific achievement; economic education; Republic of Belarus